Substrate-free, ultra-conformable PEDOT: PSS E-tattoo achieved by energy regulation on skin - Chen, Yuanfen; Zhou, Genping; Yuan, Xiaoming; Li, Chunlin; Liu, Liming; You, Hui (Biosensors & bioelectronics, 2022)
Electronic tattoo has great potential application in mobile health. Fully conformal contact between E-tattoo and skin is critical for reliable monitoring. In this paper, we reported a substrate-free, ultra-conformable PEDOT: PSS (3,4-ethylenedioxythiophene):poly(styrene-sulfonate) E-tattoo achieved by interface energy regulation on skin. The controllable gel/dry electrode mutual transformation property of PEDOT: PSS was carefully studied and reported. Then a novel transfer approach was studied to transfer thin, substrate-free PEDOT: PSS E-tattoo onto skin. Meanwhile, PEDOT: PSS E-tattoo was gelled, then dried directly on skin, regulating its bending energy, contact area, and interface adhesion energy with skin. Through this method, the critical thickness of the after-transformation dry E-tattoo that could form fully conformal contact with skin was increased by 4 times. The electrode-skin interface impedance and ECG measurement performance of the reported E-tattoo were on par with commercial Ag/AgCl gel electrodes, while offering superior comfort and reliability. The substrate-free, ultra-conformable PEDOT: PSS E-tattoo could be applied as sensing electrode for reliable monitoring in mobile health. A novel transfer method based on the dry/gel mutual transformation property of PEDOT:PSS was developed, and applied to transfer substrate-free, ultra-conformable PEDOT: PSS E-tattoo onto skin. Meanwhile electrode-skin interface energy was regulated to improve interface contact and adhesion. The ECG measurement performance of the reported E-tattoo was better than that of Ag/AgCl gel electrodes, while offering superior comfort and stability. [Display omitted] •Interface energy regulation directly on skin was applied to achieve ultra-conformable, substrate-free, strongly adhesive PEDOT: PSS E-tattoo for the first time.•Novel transfer approach to transfer thin, substrate-free PEDOT:PSS E-tattoo onto skin.•ECG measurement performance of E-tattoo is better that of commercial Ag/AgCl gel electrodes.